MAGNETICALLY MODIFIED SUGARCANE BAGASSE BIOCHAR AS CADMIUM REMOVAL AGENT IN WATER - Baharudin, Nur Izzaty Syahirah; Mohamed Noor, Noraini; Abdullah, Ezzat Chan; Othman, Raihan; Nasibab Mujawar, Mubarak (IIUM Engineering Journal, 2022)
Heavy metals are hazardous to health at certain levels. Currently, heavy metals are removed by physicochemical treatments, such as adsorption, flotation, and electrochemical deposition, and also biological treatments, such as algal biofilm reactor and anaerobic ammonium oxidation. In this study, magnetic biochar was produced to enhance the effectiveness and performance of the adsorbent for heavy metal removal. This study aimed to synthesise high-performance magnetic biochar, to determine the optimum parameters and conditions for high yield of magnetic biochar and high removal of cadmium (Cd2+) from aqueous solution, and to determine the adsorption kinetics and isotherms for Cd2+ removal. Nickel oxide (NiO)-impregnated sugarcane bagasse was subjected to slow pyrolysis to produce magnetic biochar. The impregnated metal, pyrolysis temperature, and pyrolysis time were varied to determine the optimum parameters and conditions to produce high-performance magnetic biochar. The removal of Cd2+ from aqueous solution and batch adsorption study were conducted. The synthesised magnetic biochar was characterised using field-emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area, Fourier transform infrared (FTIR), and vibrating sample magnetometer (VSM). The adsorption data agreed well with the pseudo-second-order model and followed the Langmuir isotherm model. This study achieved 88.47% removal efficiency of Cd2+ from aqueous solution. Thus, the removal of this heavy metal as a human carcinogen reduces the hazardous effects on human health and reduces the toxicity in the environment. ABSTRAK: Logam berat adalah berbahaya bagi kesihatan di peringkat tertentu. Pada masa ini, logam berat disingkirkan melalui rawatan fizikokimia, seperti penyerapan, pengapungan, dan deposit elektrokimia, dan rawatan biologikal, seperti reaktor biofilem alga dan oksidasi ammonium anerobik. Kajian ini menghasilkan biochar magnetik bagi meningkatkan keberkesanan dan prestasi penyerapan penyingkiran logam berat. Kajian ini bertujuan bagi mengsintesis biochar magnetik pada prestasi tinggi, bagi menghasilkan parameter optimum dan keadaan pengeluaran tinggi biochar magnetik dan penyingkiran tinggi kadmium (Cd2+) daripada larutan akues, dan bagi mendapatkan penyerapan kinetik dan isoterma penyingkiran Cd2+. Nikel oksida (NiO)-impregnat hampas tebu adalah berdasarkan pirolisis perlahan bagi menghasilkan biochar magnetik. Logam yang terimpregnat, suhu pirolisis dan tempoh pirolisis dipelbagaikan bagi mendapatkan parameter optimum dan keadaan bagi menghasilkan biochar magnetik berprestasi-tinggi. Penyingkiran Cd2+ daripada larutan akues dan kajian penyerapan berkumpulan telah dibuat. Biochar magnetik yang disentisis diklasifikasikan menggunakan mikroskopi elektron imbasan medan-pancaran (FESEM), tenaga sebaran X-ray (EDX), pembelauan X-ray (XRD), kawasan permukaan Brunauer-Emmett-Teller (BET), Penjelmaan Fourier inframerah (FTIR), dan sampel getaran magnetometer (VSM). Data penyerapan menunjukkan persetujuan dengan model aturan-kedua-pseudo dan mengikuti model isoterma Langmuir. Kajian ini mencapai 88.47% keberkesanan penyingkiran Cd2+ daripada larutan akues. Oleh itu, penyingkiran logam berat ini sebagai karsinogen manusia mengurangkan kesan teruk pada kesihatan manusia dan pengurangan toksik pada alam sekitar.